2011
DOI: 10.1111/j.1365-2133.2011.10224.x
|View full text |Cite
|
Sign up to set email alerts
|

Hidradenitis suppurativa: a disease of the absent sebaceous gland? Sebaceous gland number and volume are significantly reduced in uninvolved hair follicles from patients with hidradenitis suppurativa

Abstract: Our results suggest that the absence or reduced volume of the sebaceous gland may play a role in the pathogenesis of HS. The presence of fibrosis suggests that sebaceous glands are obliterated early in the pathogenesis of HS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
1
8

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(101 citation statements)
references
References 37 publications
6
86
1
8
Order By: Relevance
“…Similar changes in SGs were also found in patients with hidradenitis suppurativa/acne inversa, in whom cigarette smoking is a high risk factor [140]. In addition, ex vivo studies also reported that dioxins and benzo(a)pyrene (BaP), representative toxicants found in environmental pollutants and cigarette smoke, strongly inhibited lipogenesis in human SZ95 sebocytes and reduced the size of SGs via activation of the aryl hydrocarbon receptor (AhR) signaling pathway [141,142].…”
Section: Sebaceous Glands and Skin Skin Detoxificationsupporting
confidence: 51%
“…Similar changes in SGs were also found in patients with hidradenitis suppurativa/acne inversa, in whom cigarette smoking is a high risk factor [140]. In addition, ex vivo studies also reported that dioxins and benzo(a)pyrene (BaP), representative toxicants found in environmental pollutants and cigarette smoke, strongly inhibited lipogenesis in human SZ95 sebocytes and reduced the size of SGs via activation of the aryl hydrocarbon receptor (AhR) signaling pathway [141,142].…”
Section: Sebaceous Glands and Skin Skin Detoxificationsupporting
confidence: 51%
“…(2). Histopathology studies imply that keratin plugging of follicles is an early feature of HS, together with a lymphocytic infiltrate and an atrophy of sebaceous glands (3,4).…”
Section: Accepted For Publication 22 December 2015mentioning
confidence: 99%
“…Furthermore, studies have shown that similar to acne toll-like receptor 2 expression is increased in macrophages and dendritic cells of patients with HS [9]. However, there are several differences which exist between acne and HS including microbiology, clinical presentation, and response to treatment [7]. Overall, there is still no absolute consensus as to the etiology of HS, but the hair follicle likely plays an integral role.…”
Section: Resultsmentioning
confidence: 90%
“…recent evidence actually suggests that involvement of the follicle and thus the pilosebaceous unit is the primary event and apocrine gland involvement is a secondary phenomenon. Studies based on histopathology describe a series of events similar to the pathogenesis of acne with hyperkeratinization of the follicle leading to dilation and rupture causing dermal inflammation and bacterial colonization, sinus tract formation, and eventually scarring [7]. These similarities between the two disorders have led to the suggestion of acne inversa as a more appropriate description than HS [8].…”
Section: Resultsmentioning
confidence: 99%